English Choral Practice, 1400-1650 - Morehen, John (Cambridge Cambridge University Press, 1995)
This is the first book to survey the performing practices in English choral music in the fifteenth, sixteenth and seventeenth centuries, including the period of the English Reformation. The essays, all written by specialists in the field, consider in depth such areas as the growth and development of the 'church' choir, related issues of vocal tessitura, performing pitch, the systems of pronunciation appropriate for Latin- and English-texted music, and the day-to-day training of choristers. There is also an investigation of the local circumstances under which many of the important manuscripts of the period were compiled, which reveals an unsuspectedly close interrelationship between domestic music and music for the church. In addition, a study of surviving sources reveals that they give little more than a general guide as to their composers' and copyists' intentions.
Keywords: 15th Century (1401-1500); 16th Century (1501-1600); 17th Century (1601-1700); Choir; Choral music; Performance; Music performance technique; Pronunciation; Latin; Church music; United Kingdom